PERENCANAAN PAJAK DENGAN MEMANFAATKAN PP NO. 23 TAHUN 2018 (Studi Kasus Pada PT X di Jawa Timur) - Ronika, Zakila Cahya; Hidayah, Dini Fatihatul; Febriansyah, Ari; Yunus, Sultan Maulana; Saifuljihad, Ihsan; Widiastuti, Ni Putu Eka (ITB AAS INDONESIA, 2024)
Tax management, especially in companies, has a huge impact. Some taxes have facilities that can be utilized by taxpayers with certain conditions, one of which is PP No. 23/2018. Thus, the purpose of this research is to find out the tax planning scheme in order to utilize the PP No. 23/2018 facility. This research is a literature study study derived from journals and supported by interviews as primary research data with the object of research is a company engaged in trading and goods in East Java. It was found that there was tax evasion in the implementation of tax planning by the company in the form of a scheme that made employee salaries below PKP and fictitious directors' salaries because this affected the company's gross turnover. This is done by the company to take advantage of the facilities from PP No. 23/2018 in the form of 0.5% final income tax. Although this scheme is considered illegal (tax evasion), it is carried out as an effort by the company to provide welfare in the form of not deducting employee salaries due to the fulfillment of tax obligations and to reduce the corporate tax rate.